2013
DOI: 10.2337/dc12-2198
|View full text |Cite
|
Sign up to set email alerts
|

A 10-s Sprint Performed After Moderate-Intensity Exercise Neither Increases nor Decreases the Glucose Requirement to Prevent Late-Onset Hypoglycemia in Individuals With Type 1 Diabetes

Abstract: OBJECTIVETo determine whether performing a 10-s sprint after moderate-intensity exercise increases the amount of carbohydrate required to maintain euglycemia and prevent late-onset postexercise hypoglycemia relative to moderate-intensity exercise alone.RESEARCH DESIGN AND METHODSSeven individuals with type 1 diabetes underwent a hyperinsulinemic-euglycemic clamp and performed 30 min of moderate-intensity exercise on two separate occasions followed by either a 10-s maximal sprint effort or no sprint. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…However, many individuals prefer to exercise in the evening because of study and work commitments or for social reasons. Unfortunately, exercise in the evening is associated with a greater risk of postexercise hypoglycemia (4,9), with low blood glucose levels likely to occur particularly nocturnally (2). Incorporation of evening exercise safely into the lives of people with type 1 diabetes is thus significantly hampered by the lack of appropriate evidence necessary for informed self-management strategies.…”
mentioning
confidence: 99%
“…However, many individuals prefer to exercise in the evening because of study and work commitments or for social reasons. Unfortunately, exercise in the evening is associated with a greater risk of postexercise hypoglycemia (4,9), with low blood glucose levels likely to occur particularly nocturnally (2). Incorporation of evening exercise safely into the lives of people with type 1 diabetes is thus significantly hampered by the lack of appropriate evidence necessary for informed self-management strategies.…”
mentioning
confidence: 99%
“…With respect to this, we have shown that antecedent hypoglycaemia does not diminish the glucoregulatory response to same-day sprinting [15], and that a 10-s sprint performed after 30 min of moderate-intensity exercise does not affect the amount of exogenous carbohydrate required to maintain euglycaemia post-exercise [13]. With respect to this, we have shown that antecedent hypoglycaemia does not diminish the glucoregulatory response to same-day sprinting [15], and that a 10-s sprint performed after 30 min of moderate-intensity exercise does not affect the amount of exogenous carbohydrate required to maintain euglycaemia post-exercise [13].…”
Section: Introductionmentioning
confidence: 89%
“…Conversely, high-intensity exercise can cause hyperglycaemia [8,9]. Recent work by our group and others has shown that a 10-second (s) sprint is a useful strategy to attenuate the risk of exercise-induced hypoglycaemia [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Davey et al 37 compararam a necessidade de reposição de carboidratos em indivíduos com DM1, em duas experiências relacionadas ao exercício físico aeróbico: o primeiro grupo realizou atividade com intensidade moderada, durante 30 min; o segundo grupo realizou atividade com intensidade moderada, durante 30 min, mais 10 segundos de Sprint final. Os resultados apontaram que não houve diferença significativa em relação à necessidade de infusão de glicose, em relação aos níveis de glicemia e em relação às concentrações de insulina plasmática em ambas condições experimentais.…”
Section: Página 9 De 14unclassified